MATT BUCKNER'S PERSONALITY DEVELOPMENT IN LEXI ALEXANDER'S GREEN STREET HOOLIGANS MOVIE (2005): AN INDIVIDUAL PSYCHOLOGICAL APPROACH - HARDI, RIO (2011)
The object of this research is the movie entitled Green Street Hooligans by Lexi Alexander. The major problem of this study is "how Matt Buckner's personality development portrayed in Green Street Hooligans (2005) by Lexi Alexander" based on a Individual Psychological Approach. The researcher employs qualitative method; the researcher uses two data sources, namely primary and secondary data source. The primary da ta source is the movie itself while the secondary data source is the other sources related to the analysis such as script, books, journals, articles, and movie review. The method of data collection is library research and the technique of data collection is note taking and scene capturing. The study comes to the following conclusions. First, based on the structural analysis of each elements, it shows that the character and characterization, plot, point of view, setting of place and time, mise-en- scene, cinematography, editing, and the other technical elements have the unity and successfully relate to one another then finally are formulated into good quality of a movie. Second, the Individual Psychological analysis shows that the personality development of major character influenced by his problem and the goal of his life. His interaction with his new hooligans ' friends also gives a big contribution to his personality development. The love and attention of parents, good family and good society however are needed for the teenagers.